2019
DOI: 10.1159/000502934
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Helping Babies Breathe via Telehealth: A New Application in Rural Guatemala

Abstract: Background: Helping Babies Breathe (HBB) is a neonatal resuscitation curriculum that teaches life-saving interventions utilized in the first minutes after birth, reducing morbidity and mortality. Traditionally, it requires in-person facilitators for didactic and hands-on training. Objectives: The aim of this study was to offer HBB to nurses and nursing students in Guatemala, with the lead facilitator presenting concepts via telehealth and in-person facilitators providing hands-on demonstration. Methods: Learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…44 In settings where in-person refresher training is costly and potentially challenging, and may be even more difficult within the context of COVID-19 concerns, digital and telehealth interventions may adequately support the retention of neonatal resuscitation knowledge and skills. 45 Little is known about the feasibility and acceptability of VR as a novel educational modality for training HCWs in resource-scarce settings. Previous descriptions of mobile VR use with school-age children in LMICs suggest that mobile VR simulations can be used to demonstrate realworld phenomena, illustrate abstract concepts and motivate learners.…”
Section: Osce a Pass Ratesmentioning
confidence: 99%
“…44 In settings where in-person refresher training is costly and potentially challenging, and may be even more difficult within the context of COVID-19 concerns, digital and telehealth interventions may adequately support the retention of neonatal resuscitation knowledge and skills. 45 Little is known about the feasibility and acceptability of VR as a novel educational modality for training HCWs in resource-scarce settings. Previous descriptions of mobile VR use with school-age children in LMICs suggest that mobile VR simulations can be used to demonstrate realworld phenomena, illustrate abstract concepts and motivate learners.…”
Section: Osce a Pass Ratesmentioning
confidence: 99%
“…86 In a 3-year study on HBB program implementation in 15 regions in Tanzania, an assessment of the program's impact on neonatal mortality proved to be challenging because of the poor availability of historical, preintervention data. 25 88 Recent uses of technology to cut costs and ease logistic burden of implementation include training via video conferencing 61 and mobile apps 41 as well as the use of a highfidelity mannequin that provides feedback based on resuscitation performance. 58 HBB implementation translates into meaningfully improved skills and knowledge as demonstrated through multiple studies in which authors cite improved average OSCE scores and pass rates on knowledge assessments.…”
Section: Newborn Outcomesmentioning
confidence: 99%
“…One study did examine teaching the course via telehealth methods and demonstrated efficacy with HBB training, but did not provide a comparison to in-person learning. 6 This study offers the first direct comparison of virtual to in-person learning of HBB, to date, and demonstrates that a virtual HBB course is non-inferior to an in-person course.…”
Section: Introductionmentioning
confidence: 77%